Pengaruh Kirigami Terhadap Kemampuan Motorik Halus Anak di Taman Kanak-Kanak - Rakimahwati Rakimahwati; Nora Agus Lestari; Sri Hartati (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
The method used of research Quasi Eksperimental design. The purpose of this study was to prove the influence of kirigami to the fine motor skills of Ability of early childhood at Taman Kanak-Kanak Yayasan Amalan Parupuk Tabing Padang. Use 12 childeren in class B1 as the experiment class and use the and use the 12 children in class of B2 as control class. Data collected by teacher-made tests, in form of statements as many 5 item. The results showed that the experimental class children using kirigami had a higher average when compared with the control class that used the origami alam semesta. The average number of experimental class is 83.25 and the control class average is 76. Based on data analysis that thitung ttabel 2,161 2,07387. And than using kirigami affect the fine motor skilss of 5-6 year age in Taman Kanak-Kanak Yayasan Amalan Parupuk Tabing Padang.